2005
DOI: 10.1002/sys.20027
|View full text |Cite
|
Sign up to set email alerts
|

A reference-dependent regret model for deterministic tradeoff studies

Abstract: Today's typical multi-criteria decision analysis is based on classical expected utility theory that assumes a mythical "Rational Individual" immune to psychological influences such as anticipated regret. It is therefore in conflict with rational individuals who trade-off some benefits and forgo the alternative with the highest total classical utility for a more balanced alternative in order to reduce their levels of anticipated regret. This paper focuses on decision making under certainty. It presents a refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Moreover, the least-regret as a compromise solution is associated with higher user benefits in the short-term and lower user benefits in the long-term, likely leading to the higher political acceptability of this scenario in the short-term. Thus, considering a generalized utility combining both utility and regret in the evaluation process could be informative to decision-makers by considering the impact of different MCA models under uncertainty (16). Consequently, the proposed assessment of policy-packages are more robust and transparent compared to the existing approaches solely based on utility-maximization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the least-regret as a compromise solution is associated with higher user benefits in the short-term and lower user benefits in the long-term, likely leading to the higher political acceptability of this scenario in the short-term. Thus, considering a generalized utility combining both utility and regret in the evaluation process could be informative to decision-makers by considering the impact of different MCA models under uncertainty (16). Consequently, the proposed assessment of policy-packages are more robust and transparent compared to the existing approaches solely based on utility-maximization.…”
Section: Discussionmentioning
confidence: 99%
“…The utility-based MCA is based on the method of multi-attribute utility analysis (MAUA), a structured methodology designed to handle trade-offs among multiple objectives in a rank ordered evaluation of alternatives that reflects the decision-makers' preferences (e.g., 6,10,16,23,24). The basic assumptions of MAUA are that each alternative is characterized by a multi-attribute utility function, the alternative utilities are independent, and the attributes characterizing each alternative are independent (16).…”
Section: Utility-based Mcamentioning
confidence: 99%
“…Before developing the proposed regret and rejoicing functions, we should highlight that there is no fundamental law of nature to postulate regret or rejoicing to be concave or convex (Kujawski 2005). Therefore, as Loomes and Sugden (1982) suggested that the regret and rejoicing functions can be made mainly on the basis of empirical evidence.…”
Section: Definition 3 An Alternative X R Is Said To Be the Worst Exammentioning
confidence: 99%
“…Recently, Kujawski [2005] argued that a person's level of regret often depends explicitly on the absolute values of the utilities of the chosen and forgone alternatives rather than simply the differences. He proposed the Reference-Dependent Regret Model (RDRM) to account for this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Kujawski [2005], three properties were introduced which were argued to be necessary conditions that any effective MCDA model should satisfy. The first property is termed the "independence of dominated alternatives."…”
Section: Introductionmentioning
confidence: 99%